Music Therapy in Post-Stroke Patient Anxiety Problems: Scoping Review - Elisabeth Yunita Sofiana Mbau; Fitria Handayani; Novi Kusumaningrum (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This article uses the scoping review method, through a review of articles on music therapy interventions that have been used to reduce anxiety in post-stroke patients. Article searches are accessed through the database: CINAHL, MEDLINE, Academic search ultimate, science direct, and google scholar. Results: Music therapy can be applied to treat psychological problems such as anxiety in post-stroke patients. The results of the review of the article found 3 findings, namely: 1) music genre, 2) duration of music therapy, 3) sessions in music therapy. Music therapy to deal with anxiety problems in post-stroke patients is by paying attention to the music genre, the duration or duration of therapy, and the sessions or stages of music therapy. Music therapy intervention can be carried out by nurses as an independent intervention, which can be applied to both post-stroke patients who are still inpatient and who are undergoing rehabilitation